فعّالية طريقة القراءة لترقي كفاءة فهم المقروء لدى الطلاب في مدرسة مفتاح العلوم الشرعية بجاندونج،آغام - سلافينا, ريفا; يسرى, أوكتارينا; فبريانتا, ريتا; ريزال, إيكا (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
In this thesis, the author is looking for reading comprehension in teaching reading skill. The students understood the text only a little and most of them still feel thet studying the Arabic language is the most difficult of the lessons. And they obtained a result that did not reach the minimum standard for the obtained score. The purpose of the research is to explore the effectiveness of the reading method to improve the reading comprehension efficiency of the students at the Miftah Islamic Sciences School in Canduang, Agam. The author used experimental research to improve reading comprehension efficiency in teaching reading skill. The data collection method id observation and tests. To analyze the results of the research, the author used the T-test rule. She researched in two class, the experimen class and the control class. For the students in experimental class, the writer used the reading method in teaching the reading skill (reading comprehension). While in the discipline class, I did not aplly this method and taught the method of grammar and translation. The result of teaching reading comprehension among students in the eleventh semester after using this method. The everage result of the post-test in the experimental class is 88, as for the average result of the post-test in the control class,it is 75,16. The author found that result of the t-account is (8,600) and result of the table is (2,90), so the result of the t-account is greater than the t-table, the diffrerence between them means (5,7), and the author came to the conclusion that using the method of reading is effective to improve the comprehension of the reading comprehension among students at Miftah Islamic Sciences School in Cnduang, Agam.